Low temperature firing and microwave dielectric properties of Bi4−xGe3O12−1.5x ceramics. Issue 2 (1st February 2017) - Ma, Xing-Hua; Kweon, Sang-Hyo; Nahm, Sahn; Kang, Chong-Yun; Yoon, Seok-Jin; Kim, Young-Sik
Abstract: Dense Bi4 Ge3 O12 ceramics sintered at 850 °C had a relative permittivity ( ε r ) of 15.7, temperature coefficient of resonant frequency ( τ f ) of −24.2 ppm/°C, and quality factor ( Q × f ) of 28, 361 GHz. However, because of the existence of Bi12 GeO20 as a secondary phase, the microwave dielectric properties of Bi4 Ge3 O12 would be degraded. Therefore, to avoid the formation of the Bi12 GeO20 secondary phase, Bi2 O3 -deficient Bi4- x Ge3 O12-1.5 x ceramics with 0.1≤ x ≤0.6 were sintered at 850 °C. A single phase of Bi3.6 Ge3 O11.4 ( x =0.4) ceramic sintered at 850 °C for 5 h without any secondary phase exhibited suitable microwave dielectric properties for a ceramic substrate: ε r =14.9, τ f =−9.5 ppm/°C, and Q × f =53, 277 GHz.